Insulin sensitivity and sepsis score: A correlation between model-based metric and sepsis scoring system in critically ill patients - Suhaimi F.M.; Chase J.G.; Pretty C.G.; Shaw G.M.; Razak N.N.; Jamaludin U.K. (Elsevier Ltd, 2023)
Diagnosis; Intensive care units; Clinical conditions; Critically-ill patients; Insulin sensitivity; Multiple comparison; Real-time diagnosis; Sepsis; Sepsis score; Systemic inflammatory response syndromes; Insulin; insulin; adult; aged; APACHE; Article; clinical article; controlled study; critically ill patient; diagnostic value; disease assessment; female; human; insulin sensitivity; male; modified hourly sepsis score; predictive value; priority journal; scoring system; sensitivity and specificity; sepsis